The Role of Blockchain in Addressing Unlicensed Mining: Opportunities and Challenges for Law Enforcement - Baginda Khalid Hidayat Jati; Esmi Warassih Pujirahayu; Tedi Asmara (Dinasti Research, 2024)
Digital transformation through blockchain technology offers new potential for combating illegal mining in Indonesia, but it also presents challenges for the legal profession. According to 2023 data from the Ministry of Energy and Mineral Resources (ESDM), there are 2,741 unauthorized mining (PETI) locations, with 1,215 designated as People's Mining Areas (WPR). This study aims to explore how blockchain can be integrated into the legal system to enhance surveillance and law enforcement against illegal mining. Utilizing a qualitative-normative approach and content analysis, the research investigates blockchain's role in recording transactions and verifying the legality of mining activities. The findings reveal that blockchain improves transparency in mining oversight but requires regulatory adjustments and enhancements in law enforcement's technical capabilities. The study concludes that cross-sector collaboration among government, private industry, and academia is crucial to developing a legal framework that supports blockchain implementation, while providing targeted guidance to communities involved in illicit mining.